Health‐risk behaviours among Indigenous Australians with diabetes: A study in the integrated Diabetes Education and Eye Screening (iDEES) project. (17th January 2022) - Atkinson‐Briggs, Sharon; Jenkins, Alicia; Ryan, Christopher; Brazionis, Laima
Abstract: Aim: To assess the prevalence of modifiable health‐risk behaviours among Indigenous Australian adults with diabetes attending a regional Victorian Indigenous primary‐care clinic. Design: A cross‐sectional observational single‐site study. Methods: As part of a multi‐study project we administered the Smoking, Nutrition, Alcohol consumption, Physical activity and Emotional wellbeing (SNAPE) survey tool during the study baseline visit to methodically capture health‐related behavioural data in the nurse‐led integrated Diabetes Education and Eye Screening (iDEES) project in a regional Indigenous primary healthcare setting between January 2018 and March 2020. This descriptive SNAPE study helps address the lack of health behaviour data for Indigenous people with diabetes. Results: Of 172 eligible adults, 135 (79%) were recruited to the iDEES study, 50 (37%) male. All participated in at least one survey. Median (range) age was 56 (46–67) years; 130 (96%) had Type 2 diabetes of median [IQR] duration 6 (2–12) years. All 135 provided smoking data; 88 (65%) completed all surveys. Forty‐nine (36%) and 29 (22%) were current or former smokers, respectively; 5 (6%) met vegetable intake guidelines, 22 (25%) met fruit intake guidelines; 38 [43%] drank alcohol in the past year. On average, participants walked for ≥10 min at a time 4 days/week and sat for an average of 8 h on weekdays; 35 (40%) had minimal‐mild, and 30 (34%) had moderate‐severe depressive symptoms. Conclusion: Suboptimal modifiable health‐risk behaviours and depressive symptoms are common in Indigenous Australian adults with diabetes. Impact: Orderly assessment and reporting of health‐risk behaviours using a single multi‐component survey instrument (SNAPE tool) during a nurse‐led diabetes education clinical visit is feasible and efficient. Such data may facilitate personalised interventions and improve diabetes management at both individual and health service levels.